Early onset neonatal sepsis and its associatited factors: a cross sectional study - Ketsela Lemma; Yemane Berhane (BMC, 2024)
Abstract Background Sepsis is the 3rd leading cause of neonatal mortality in Ethiopia contributing to 16% of neonatal death. In a hospital study, neonatal sepsis was the leading diagnosis at admission and the second leading cause of neonatal death at the neonatal intensive care unit. Among other factors repeated vaginal examination during labor is known to contribute to sepsis in low-income settings. However, there is limited evidence in the Ethiopian setting. Objective The objective of this study was to examine the association between early-onset neonatal sepsis and repeated vaginal examinations. Methods The study was conducted at Gandhi Memorial Hospital, a public maternity and newborn care hospital. We followed 672 mother-newborn pairs by phone until 7 days of age to detect clinical sepsis. Data were analyzed using SPSS version 20 software. Adjusted odds ratio risk (AOR) with a corresponding 95% confidence interval (CI) was used to show the strength of associations and variables with p-value < 0.05 were considered to be statistically significant. Results The incidence of early-onset neonatal sepsis was found to be 20.83% (95% CI 17.60, 24.00). Having a frequent vaginal examination (four or more times) during labor and delivery, prolonged rupture of membranes, induced labor and gestational age < 37 weeks were strongly associated with the development of early-onset neonatal sepsis, (AOR 2. 69;95 CI: 1.08, 6.70) AOR 5.12(95% CI 1.31, 20.00), AOR of 5.24 (95% CI 1.72, AOR4.34 (95% CI 1.20, 15.68), 16.00), respectively. Conclusion Frequent digital vaginal examination prolonged rupture of membranes, induced labor and gestational age < 37 weeks significantly increases the risk of early onset neonatal sepsis. We also recommend further study using neonatal blood culture to better diagnose early onset neonatal sepsis objectively.